Conversion of actual flue gas CO2 via cycloaddition to propylene oxide catalyzed by a single-site, recyclable zirconium catalyst. (July 2017) - Kelly, Michael J.; Barthel, Alexander; Maheu, Clement; Sodpiban, Ounjit; Dega, Frank-Blondel; Vummaleti, Sai V.C.; Abou-Hamad, Edy; Pelletier, Jeremie D.A.; Cavallo, Luigi; D'Elia, Valerio; Basset, Jean-Marie
Graphical abstract: Highlights: Zirconium-based catalysts supported on dehydroxylated silica were prepared and fully characterized. The materials could be employed as heterogeneous, recyclable systems for the cycloaddition of CO2 to epoxides. The catalyst were active under mild conditions, actual flue gas can be used as a source of impure CO2 . DFT calculations were carried out to investigate the mechanistic aspects. Abstract: A reusable zirconium-based catalyst for the cycloaddition of CO2 to propylene oxide (PO) was prepared by the surface organometallic chemistry (SOMC) methodology. Accordingly, well-defined amounts of the ZrCl4 ·(OEt2 )2 precursor were grafted on the surface of silica dehydroxylated at 700 °C (SiO2-700 ) and at 200 °C (SiO2-200 ) in order to afford surface coordination compounds with different podality and chemical environment. The identity of the surface complexes was thoroughly investigated by FT-IR, elemental microanalysis and solid state NMR and applied as a recoverable and reusable heterogeneous catalyst for the title reaction using pure CO2 and flue gas samples from a cement factory. The observed catalytic activity for the isolated zirconium complexes is rationalized by means of systematic DFT calculations.